Arbuscular mycorrhiza mitigates zinc stress on Eucalyptus grandis through regulating metal tolerance protein gene expression and ionome uptake - Han, Li-Na; Wang, Si-Jia; Chen, Hui; Ren, Ying; Xie, Xian-An; Wang, Xing-Yang; Hu, Wen-Tao; Tang, Ming (Frontiers in Plant Science, 2022)
Arbuscular mycorrhizal fungi are symbionts of most terrestrial plants and enhance their adaptability in metal-contaminated soils. In this study, mycorrhized and non-mycorrhized Eucalyptus grandis were grown under different Zn treatment. After six weeks treatment, the growing status and ionome content of plants, as well as the expression patterns of metal tolerance proteins and auxin biosynthesis related genes were measured. In this study, mycorrhized E. grandis showed higher biomass and height at high Zn level compared with non-mycorrhized plants. And AM plants accumulated P, Mg and Mn in roots and P, Fe and Cu in shoots, which indicating that AM fungi facilitate the uptake of ionome nutrients to promote plant growth. In addition, mycorrhiza upregulated the expression of EgMTP1 and EgMTP7, whose encoding proteins were predicated to be located at vacuolar membrane. Meanwhile, Golgi membrane transporter EgMTP5 was also induced in AM shoot. Our results suggest that AM likely mitigates Zn toxicity through sequestrating excess Zn into vacuolar and Golgi. Furthermore, the expression of auxin biosynthesis related genes was facilitated by AM, and this probably be another approach for Zn tolerance.